THE CONCEPT OF IMPLEMENTATION CREDIT AGREEMENTS THROUGH ONLINE MEDIA IN LEGAL PERSPECTIVE - Azharuddin Azharuddin; Elvira Fitriani Pakpahan; Riris Swastriona Purba (International Journal of Latin Notary, 2021)
The Indonesian state’s philosophical foundation is Pancasila (Five principles) and The 1945 Constitution which guarantees and provides legal protection for all Indonesian people. The provision of credit to debtors is contained in a credit agreement with a legal basis that still refers to Article 1320 of the Civil Code. Credit Agreement in banking is a standard agreement or standard with clauses determined by the bank. Legal subjects are creditors and debtors, namely individuals, business entities and legal entities. The notary has the authority to make an authentic deed for the parties who need it in terms of proof. There are two legal powers of proof in an authentic deed, namely formal and material. The granting of credit between the creditor (bank) and the debtor will be stated in the deed. The process of binding credit or implementing a credit agreement at a bank will require the services of a Notary and Land Deed Maker (PPAT) in binding debtor credit guarantees which will be adjusted to the provisions of each bank in the bank's operational standards for each credit facility and credit limit given to individual debtors, business entities and legal entities. The terms of implementing the credit agreement have not regulated offline media or online media and how the protection is provided to banks and debtors if the credit agreement is made online and the role of the Notary/PPAT as a general official in supporting the online credit agreement implementation process.